1992
DOI: 10.7164/antibiotics.45.1268
|View full text |Cite
|
Sign up to set email alerts
|

Vermixocins A and B, two novel metabolites from Penicillium vermiculatum.

Abstract: VermixocinsA and B, 3-(r-hydroxy-3'-methylbutyl)-and 3-(r-acetoxy-3'-methylbutyl)-l lhydroxy-4-methoxy-9-methyl-5//,7/f-dibenzo [c,/] respectively. A new strain, specified B 5, selected from the above mentioned parental strain formed dehydroaltenusin only4). This compoundin addition to other polyketide metabolites was isolated from the mycelium of T. flavus (ATCC52201) grown on a malt extract medium5). Two new minor metabolites designated vermixocins A (1) and B (2) were found in the mycelium of P. vermiculatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Compound 2, according to its MS, IH and 13CNMR spectra, was identical with [2E,7E]-4,9-dioxo-2,7-decadienoic acid, which was recently identified in a mixture of compounds after vermiculin (1) degradation in boiling acetic acid [5]. bound to sp 2 carbons together with unresolved signals of four methylene protons 2.29 ppm) overlapping with a signal of one methyl group and that of one methylene group (1.68 ppm) were observed in the 1H NMR spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 2, according to its MS, IH and 13CNMR spectra, was identical with [2E,7E]-4,9-dioxo-2,7-decadienoic acid, which was recently identified in a mixture of compounds after vermiculin (1) degradation in boiling acetic acid [5]. bound to sp 2 carbons together with unresolved signals of four methylene protons 2.29 ppm) overlapping with a signal of one methyl group and that of one methylene group (1.68 ppm) were observed in the 1H NMR spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…In the same years [18,19] it was found that isoindolo[1,2-b]benz-3-azepin-5-ones 12 exhibit cytotoxic activity toward cells affected by leukemia. The last fact and also the unique structure make these compounds interesting subjects for the synthesis of various biologically active compounds.…”
Section: Synthesis Of Isoindolo[12-b]benz-3-azepinesmentioning
confidence: 99%
“…The dibenzofuran had the same UV spectrum as karnatakafurans A and B (Manniche et al 2004), but was more apolar. Penicillide and purpactins (also called vermixocins) are related extrolites that have been isolated from several Talaromyces species, including T. derxii, T. purpurogenus and T. flavus (Sassa et al 1974;Suzuki et al 1991;Proksa et al 1992). These compounds have very high levels of bioactivity, and are inhibitors of acylCoA:cholesterol acyltransferases and calpain (Tomoda et al 1991;Chung et al 1998).…”
Section: Taxonomymentioning
confidence: 99%